(untitled) (Global Journal of Science Frontier Research, 2016)
In the article suggests the conclusion of classical space-time of the real physical laws discovered by Johannes Kepler in the analysis of long-term astronomical observations of Tycho Brahe. Rather than lay a priori given space-time at all the theoretical constructs are invited to rely on the real physical picture of the world, as set out in Metaphysics I. Kepler and will be further developed in the works of Isaac Newton, Albert Einstein and Arthur Eddington. The article argues that the agenda set by modern fundamental theoretical physics problem of withdrawal of the classical space-time representations of the concepts and laws of physics of the microscopic physics, first tried to constructively implement A. Eddington in his latest work Fundamental theory. The article deals with the boundary conditions for Einstein’s general theory of relativity. Einstein’s equations are invariant and are applicable only to describe the reversible processes in equilibrium systems. The fundamental error in Einstein’s general relativity is to deny the existence of the interaction and the exchange of energy between the system and the environment (ether) and, consequently, a violation of the law of conservation of energy.